Eco-efficiency index analysis of single story structure of reinforced concrete house using economical and environmental score approach - Hamid, M.S.A. (Institute of Physics Publishing, 2019)
Reinforced concrete structure is widely used in Malaysia as a common structural system of a building. As a common understanding, reinforced concrete is also known as a composite structure that combined two type of materials which is concrete and steel. Due to rapid development of residential houses, this situation was creating to higher energy consumption by producing high content embodied carbon emission Therefore, three main criteria should be considered in sustainable development that is economic, environment and social in order to produce better environment. This study was developed to produce eco-efficiency design of single story residential house for different optimization of concrete characteristic strength by using economical score and environmental score analysis method. Finding was recorded blast furnace slag reinforced concrete produce an eco-efficiency design than fly ash reinforced concrete due to positive impact to the economical and environmental criteria. Therefore, it can be concluding that waste materials need to be analyzed as an alternative material in concrete because it may produce high content of embodied carbon that give negative impact to the environment. Â© Published under licence by IOP Publishing Ltd.